Composite positive electrode of all-solid-state lithium-ion battery and all-solid-state lithium-ion battery
The composite positive electrode with a conductive coating and optimized composition addresses the mechanical failure and impedance issues in all-solid-state lithium-ion batteries, enhancing conductivity and mechanical stability to improve battery performance.
Patent Information
- Application Number
- CN202410222982.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-28
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-02-28
AI Technical Summary
All-solid-state lithium-ion batteries face issues with loose particle bonding and increased impedance due to volume changes in the positive electrode material, leading to reduced battery capacity and cycle life, which existing methods to address these issues increase cost and reduce energy density.
A composite positive electrode with a conductive coating on the current collector and a positive electrode material layer comprising a positive electrode active material, halide solid electrolyte, conductive agent, and binder, optimized by specific thickness, particle size ratio, and compaction density to improve conductivity and mechanical stability.
Enhances the bonding strength between the positive electrode material and current collector, reduces interface impedance, and improves the rate and cycle performance of the battery.
Smart Images

Figure BDA0004718708450000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a composite positive electrode of an all-solid-state lithium-ion battery and an all-solid-state lithium-ion battery. Background Art
[0002] With the increasing demand for battery life and safety in electric vehicles and other fields, all-solid-state lithium-ion batteries have attracted people's attention. Compared with commercial liquid lithium-ion batteries, all-solid-state lithium-ion batteries use solid electrolytes instead of traditional organic flammable electrolytes, which have significantly improved safety and energy density.
[0003] However, during the charge and discharge cycle of all-solid-state lithium-ion batteries, the volume of the positive electrode material particles will inevitably change, resulting in loose bonding between particles, generating pores, and hindering the transmission channels of lithium ions and electrons. At the same time, the volume change of the positive electrode material will cause it to peel off from the current collector, which will greatly increase the impedance of the battery and reduce the battery capacity and cycle life. Compared with liquid lithium-ion batteries, all-solid-state lithium-ion batteries cannot spontaneously fill the pores of particles with a flowable electrolyte, so the problem of contact deactivation between particles is particularly serious. At present, the above-mentioned mechanical failure problem is generally alleviated by applying sufficiently high pressure to the battery during the cycle, but this method increases the cost of the battery, reduces the overall energy density of the battery, and is difficult to apply on a large scale in the terminal.
[0004] Therefore, it is necessary to provide a composite positive electrode for an all-solid-state lithium-ion battery and an all-solid-state lithium-ion battery, optimize the conductivity of the composite positive electrode material and its mechanical stability during the cycle process, and thus improve the rate performance and cycle performance of the battery. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a composite positive electrode of an all-solid-state lithium-ion battery and an all-solid-state lithium-ion battery, which optimizes the conductivity of the composite positive electrode material and its mechanical stability during the cycle process, thereby improving the battery's rate performance and cycle performance.
[0006] A first aspect of the present invention provides a composite positive electrode for an all-solid-state lithium-ion battery.
[0007] Specifically, the composite positive electrode includes a current collector with a conductive coating on its surface and a positive electrode material layer disposed on the current collector;
[0008] The positive electrode material layer includes a positive electrode active material, a halide solid electrolyte, a conductive agent, and a binder; the composite positive electrode meets the following conditions:
[0009] 0.4≤(d×k) / c≤40, and 0.1≤d≤5, 0.1≤k≤50, 1≤c≤5;
[0010] Where d is the thickness of the conductive coating in μm; k is the particle size D of the positive electrode active material and the halide solid electrolyte 50 ratio; c is the compaction density of the positive electrode active material, in g / cm 3 .
[0011] Preferably, the thickness of the conductive coating is 0.1-5 μm.
[0012] Further preferably, the thickness of the conductive coating is 0.5-3 μm.
[0013] Preferably, the conductive coating includes at least one of a carbon material and a conductive polymer; the carbon material includes at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fiber, and carbon black; the conductive polymer includes at least one of polyacetylene, polyaniline, polypyrrole, and polythiophene.
[0014] Preferably, the particle size D of the positive electrode active material and the halide solid electrolyte is 50 The ratio is (0.5~40):1.
[0015] Further preferably, the particle size D of the positive electrode active material and the halide solid electrolyte is 50 The ratio is (1~25):1.
[0016] Preferably, the particle size D of the positive electrode active material is 50 0.5~50μm.
[0017] More preferably, the particle size D of the positive electrode active material is 50 2~20μm.
[0018] Preferably, the positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich layered oxide.
[0019] Preferably, the particle size D of the halide solid electrolyte is 50 0.1~10μm.
[0020] Further preferably, the particle size D of the halide solid electrolyte is 50 0.2~5μm.
[0021] Preferably, the halide solid electrolyte is Li a MX b, wherein M is selected from at least one of Al, Y, Ga, In, Er, Sc, Ti, Zr, and La, X is selected from at least one of F, Cl, Br, and I, 0≤a≤10, and 1≤b≤13.
[0022] Preferably, the compaction density of the positive electrode active material is 1.5 to 3.3 g / cm 3 .
[0023] Further preferably, the compaction density of the positive electrode active material is 1.8 to 3.0 g / cm 3 .
[0024] Preferably, the conductive agent includes at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fiber, and carbon black.
[0025] Preferably, the preparation method of the current collector includes the following steps: dissolving a certain ratio of carbon material or conductive polymer with a binder in an appropriate solvent, stirring to form a coating, applying the coating on the current collector, and then drying it, the oven temperature is 70-100°C, the drying time is 5-10 minutes, to obtain a current collector with a conductive coating on the surface.
[0026] Preferably, the preparation method of the composite positive electrode comprises the following steps: mixing the positive electrode active material, the halide solid electrolyte, the conductive agent and the binder in a certain proportion, using dry electrode technology or conventional wet coating technology to make a positive electrode sheet with a thickness of about 100 to 300 μm, and then compounding the positive electrode sheet with a current collector having a conductive coating on the surface to obtain a composite positive electrode.
[0027] A second aspect of the present invention provides an all-solid-state lithium-ion battery.
[0028] Specifically, the all-solid-state lithium-ion battery comprises the composite positive electrode described in the first aspect, a first solid electrolyte layer, a second solid electrolyte layer and a negative electrode;
[0029] The first solid electrolyte layer is located between the composite positive electrode and the second solid electrolyte layer;
[0030] The second solid electrolyte layer is located between the negative electrode and the first solid electrolyte layer.
[0031] Preferably, the first solid electrolyte layer comprises a halide solid electrolyte and a binder;
[0032] The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyacrylate, nitrile rubber, and styrene-butadiene rubber.
[0033] Preferably, the second solid electrolyte layer comprises a sulfide electrolyte and a binder;
[0034] The sulfide electrolyte includes thio-LISICON, Li 10 G 2 S 12 , Li 10 SiP 2 S 12 , Li 3 PS 4 , Li 7 P 3 S 11 , Li 7-a PS 6-a X a At least one of;
[0035] Wherein X is at least one of Cl, Br and I; a is 0.5 to 2.
[0036] Preferably, the negative electrode includes at least one of carbon material, silicon-based material, lithium titanate, metallic tin, metallic lithium, metallic indium, tin alloy, and lithium-indium alloy.
[0037] Preferably, the method for preparing the first solid electrolyte layer and the second solid electrolyte layer comprises the following steps:
[0038] The solid electrolyte layer is prepared using a dry electrode film forming technology or a wet coating technology, wherein:
[0039] The dry electrode film making technology is as follows: a halide solid electrolyte or a sulfide electrolyte, a conductive agent and a binder are mixed in a certain proportion, and then rolled to form an electrolyte layer with a thickness of 30 to 200 μm;
[0040] The wet coating technology is as follows: a halide solid electrolyte or a sulfide electrolyte, a conductive agent and a binder (nitrile rubber) are dissolved in a xylene and butyl butyrate solution in a certain proportion, and the slurry is scraped onto a PET film after stirring. After being kept at room temperature for 5 to 15 minutes, the slurry is transferred to a vacuum oven at a temperature of 60 to 100°C for vacuum drying overnight to obtain a first solid electrolyte layer and a second solid electrolyte layer.
[0041] Preferably, the preparation method of the negative electrode comprises the following steps: mixing the carbon material and the binder in NMP, using dry electrode film forming technology or wet coating technology to form a negative electrode layer with a thickness of about 5 to 100 μm, and then compounding the negative electrode layer with a current collector to obtain a negative electrode.
[0042] Preferably, the preparation method of the all-solid-state lithium-ion battery comprises the following steps: cutting the prepared composite positive electrode, the first solid electrolyte layer, the second solid electrolyte layer, and the negative electrode into squares with side lengths of 15-25 mm, 25-35 mm, 25-35 mm, and 20-30 mm, respectively, and then welding the upper pole ears of the composite positive electrode and the negative electrode, placing the negative electrode-second solid electrolyte layer-first solid electrolyte layer-composite positive electrode in sequence from top to bottom, using a pressure of 300-500 MPa to press and form, and placing them in an aluminum-plastic film bag, and then vacuum packaging to obtain an all-solid-state lithium-ion battery with a soft-pack cell.
[0043] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0044] (1) By providing a conductive coating on the surface of the composite positive electrode current collector, the bonding strength between the positive electrode material and the current collector is improved, while the contact area between the positive electrode active material and the current collector is increased, thereby reducing the interface impedance of the current collector.
[0045] (2) By compounding the positive electrode active material with a halide solid electrolyte with high oxidation stability and good ductility, and regulating its particle size ratio and compaction density, the closeness of the particle contact is increased, the porosity of the positive electrode material is reduced, and its mechanical stability and conductive properties are improved. DETAILED DESCRIPTION
[0046] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0047] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0048] Example 1
[0049] An all-solid-state lithium-ion battery and a preparation method thereof.
[0050] The all-solid-state lithium-ion battery comprises a composite positive electrode, a first solid electrolyte layer, a second solid electrolyte layer and a negative electrode; the first solid electrolyte layer is located between the composite positive electrode and the second solid electrolyte layer; the second solid electrolyte layer is located between the negative electrode and the first solid electrolyte layer.
[0051] The preparation method comprises the following steps:
[0052] Composite positive electrode: Graphene and polyvinylidene fluoride in a mass ratio of 98.5:1.5 were dissolved in NMP, stirred to form a coating, the coating was applied on an aluminum foil current collector, and then dried at an oven temperature of 70°C for 10 minutes to obtain a current collector with a conductive coating on the surface.
[0053] Then the positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O 2 , Li 3 InCl 6 , carbon fiber and polytetrafluoroethylene are mixed in a mass ratio of 70:30:1:1, and a positive electrode sheet with a thickness of 100-110 μm is made using dry electrode technology or conventional wet coating technology. The positive electrode sheet is then compounded with a current collector having a conductive coating on its surface to obtain a composite positive electrode.
[0054] The conductive coating thickness d is 0.1 μm; LiNi 0.8 Co 0.1 Mn 0.1 O 2 With Li 3 InCl 6 Particle size D 50 The ratio k is 20; the compaction density c of the positive electrode active material is 2.4g / cm 3 ; That is, (d×k) / c is 0.83.
[0055] The first solid electrolyte layer: using dry electrode film making technology, Li 3 InCl 6 It is mixed with polytetrafluoroethylene in a mass ratio of 99:1 and rolled to form an electrolyte layer with a thickness of 50 to 60 μm.
[0056] The second solid electrolyte layer: using dry electrode film making technology, Li 6 PS 5 Cl and polytetrafluoroethylene are mixed in a mass ratio of 99:1 and rolled to form an electrolyte layer with a thickness of 50 to 60 μm.
[0057] Negative electrode: The nanocarbon material and styrene-butadiene rubber were mixed in NMP at a mass ratio of 98.5:1.5, and a negative electrode layer with a thickness of 80 to 90 μm was prepared using a wet coating technique. The negative electrode layer was then composited with a copper foil current collector to obtain a negative electrode.
[0058] The prepared composite positive electrode, first solid electrolyte layer, second solid electrolyte layer, and negative electrode were cut into squares with side lengths of 20 mm, 30 mm, 30 mm, and 25 mm, respectively. Then, the composite positive electrode and the negative electrode were welded to the upper pole ears, and the negative electrode-second solid electrolyte layer-first solid electrolyte layer-composite positive electrode were placed in sequence from top to bottom. The molding was carried out using a pressure of 300 MPa for 10 minutes, and the molds were placed in aluminum-plastic film bags and vacuum packaged to obtain a soft-pack cell all-solid-state lithium-ion battery.
[0059] Example 2
[0060] An all-solid-state lithium-ion battery and a preparation method thereof.
[0061] The difference between Example 2 and Example 1 is that the thickness d of the conductive coating is 0.5 μm; that is, (d×k) / c is 4.2.
[0062] Example 3
[0063] An all-solid-state lithium-ion battery and a preparation method thereof.
[0064] The difference between Example 3 and Example 1 is that the thickness d of the conductive coating is 2.0 μm; 0.8 Co 0.1 Mn 0.1 O 2 With Li 3 InCl 6 Particle size ratio D 50 k is 0.5; that is, (d×k) / c is 0.42.
[0065] Example 4
[0066] An all-solid-state lithium-ion battery and a preparation method thereof.
[0067] The difference between Example 4 and Example 1 is that the thickness d of the conductive coating is 2.0 μm; the compaction density c of the positive electrode active material is 1.6 g / cm 3 ; That is, (d×k) / c is 25.0.
[0068] Example 5
[0069] An all-solid-state lithium-ion battery and a preparation method thereof.
[0070] The difference between Example 5 and Example 1 is that the thickness d of the conductive coating is 2.0 μm; that is, (d×k) / c is 16.7.
[0071] Example 6
[0072] An all-solid-state lithium-ion battery and a preparation method thereof.
[0073] The difference between Example 6 and Example 1 is that the thickness d of the conductive coating is 2.0 μm; the compaction density c of the positive electrode active material is 3.0 g / cm 3 ; That is, (d×k) / c is 13.3.
[0074] Example 7
[0075] An all-solid-state lithium-ion battery and a preparation method thereof.
[0076] The difference between Example 7 and Example 1 is that the thickness d of the conductive coating is 2.0 μm; 0.8 Co 0.1 Mn 0.1 O 2 With Li 3 InCl 6 Particle size ratio D 50 k is 40; that is, (d×k) / c is 33.3.
[0077] Comparative Example 1
[0078] An all-solid-state lithium-ion battery and a preparation method thereof.
[0079] The difference between Comparative Example 1 and Example 1 is that no conductive coating is provided.
[0080] Comparative Example 2
[0081] An all-solid-state lithium-ion battery and a preparation method thereof.
[0082] The difference between Comparative Example 2 and Example 1 is that the thickness d of the conductive coating is 2.0 μm; 0.8 Co 0.1 Mn 0.1 O 2 With Li 3 InCl 6 Particle size ratio D 50 k is 0.2; that is, (d×k) / c is 0.17.
[0083] Comparative Example 3
[0084] An all-solid-state lithium-ion battery and a preparation method thereof.
[0085] The difference between Comparative Example 3 and Example 1 is that the thickness d of the conductive coating is 5.0 μm; the compaction density c of the positive electrode active material is 1.6 g / cm 3 ; That is, (d×k) / c is 62.5.
[0086] Battery performance test:
[0087] The all-solid-state lithium-ion battery samples obtained in Examples 1 to 7 and Comparative Examples 1 to 3 were tested at room temperature:
[0088] 1. Rate performance test:
[0089] Take 3 batteries from each group, first charge to 4.25V (cut-off current is 0.05C) with 0.1C constant current and constant voltage, let it stand for 5 minutes, then discharge to 2.5V with 0.1C, and record the 0.1C discharge capacity; let it stand for 5 minutes, charge to 4.25V (cut-off current is 0.05C) with 1C constant current and constant voltage, let it stand for 5 minutes, then discharge to 2.5V with 1C, and record the 1C discharge capacity; 1C discharge capacity retention rate (%) = 1C discharge capacity / 0.1C discharge capacity × 100%; The 1C discharge capacity retention rate of the final test is the average value of the capacity retention rates of the 3 test batteries, and the results are shown in Table 1.
[0090] 2. Cycle performance test:
[0091] Three batteries were taken from each group, first charged to 4.25V (cut-off current was 0.05C) with 0.1C constant current and constant voltage, left to stand for 5 minutes, then discharged to 2.5V with 0.1C, left to stand for 5 minutes, and then started 0.5C charge and discharge cycle test; 0.5C cycle 100 cycles capacity retention rate (%) = 100th cycle discharge capacity / first cycle discharge capacity × 100%; the final test 0.5C cycle 100 cycles capacity retention rate is the average capacity retention rate of the 3 test batteries, and the results are shown in Table 1.
[0092] Table 1 Rate performance and cycle performance test results of the embodiments and comparative examples
[0093]
[0094] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution obtained by any modification, equivalent replacement, improvement, etc. made by a person skilled in the art based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art shall be within the scope of protection determined by the claims.
Claims
1. A composite positive electrode for an all-solid-state lithium-ion battery, characterized in that: The composite positive electrode comprises a current collector with a conductive coating on its surface and a positive electrode material layer disposed on the current collector; The positive electrode material layer includes a positive electrode active material, a halide solid electrolyte, a conductive agent, and a binder; the composite positive electrode meets the following conditions: 0.4≤(d×k) / c≤40, and 0.1≤d≤5, 0.1≤k≤50, 1≤c≤5; Where d is the thickness of the conductive coating in μm; k is the particle size D of the positive electrode active material and the halide solid electrolyte 50 ratio; c is the compaction density of the positive electrode active material, in g / cm 3 ; The particle size D of the positive electrode active material 50 0.5~50μm; The particle size D of the halide solid electrolyte 50 0.1~10μm.
2. The composite positive electrode according to claim 1, characterized in that The conductive coating includes at least one of a carbon material and a conductive polymer; the carbon material includes at least one of acetylene black, graphene, graphyne, carbon nanotubes, carbon fiber, and carbon black; the conductive polymer includes at least one of polyacetylene, polyaniline, polypyrrole, and polythiophene.
3. The composite positive electrode according to claim 1, characterized in that The positive electrode active material includes at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich layered oxide.
4. The composite positive electrode according to claim 1, characterized in that: The halide solid electrolyte is Li a MX b , wherein M is selected from at least one of Al, Y, Ga, In, Er, Sc, Ti, Zr, and La, X is selected from at least one of F, Cl, Br, and I, 0≤a≤10, and 1≤b≤13.
5. The composite positive electrode according to claim 1, characterized in that: The compaction density of the positive electrode active material is 1.5 to 3.3 g / cm 3 .
6. An all-solid-state lithium-ion battery, characterized in that: The all-solid-state lithium-ion battery comprises the composite positive electrode according to any one of claims 1 to 5, a first solid electrolyte layer, a second solid electrolyte layer and a negative electrode; The first solid electrolyte layer is located between the composite positive electrode and the second solid electrolyte layer; The second solid electrolyte layer is located between the negative electrode and the first solid electrolyte layer.
7. The all-solid-state lithium-ion battery according to claim 6, characterized in that: The first solid electrolyte layer includes a halide solid electrolyte and a binder; The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyacrylate, nitrile rubber, and styrene-butadiene rubber.
8. The all-solid-state lithium-ion battery according to claim 6, characterized in that: The second solid electrolyte layer includes a sulfide electrolyte and a binder; The sulfide electrolyte includes thio-LISICON, Li 10 GeP2S 12 , Li 10 SiP2S 12 、Li3PS4、Li7P3S 11 , Li 7- a PS 6-a X a At least one of; Wherein X is at least one of Cl, Br and I; a is 0.5 to 2.
Citation Information
Patent Citations
Positive electrode for all-solid-state battery and all-solid-state battery
CN115411217A
